IMPLEMENTATION OF EDUCATIONAL REFORMS DURING THE 1990s IN POLAND: OBSTACLES AND CONDITIONS - Hryshchuk, Yulia (The Modern Higher Education Review, 2018)
The article describes the main directions of educational reforms during the 1990-ies in Poland; analyzed the structure of the educational system in Poland; examined changes being implemented in the system of training teachers; identified obstacles and conditions for implementing reforms during transition period.